2017
DOI: 10.1111/jgs.14806
|View full text |Cite
|
Sign up to set email alerts
|

The Hispanic Paradox: Race/Ethnicity and Nativity, Immigrant Enclave Residence and Cognitive Impairment Among Older US Adults

Abstract: Hispanics, and particularly foreign-born Mexican Americans, have been shown to fare better across a range of health outcomes than might be expected given the generally higher levels of socioeconomic disadvantage in this population, a phenomena termed the “Hispanic Paradox”. Previous research on social disparities in cognitive aging, however, has been unable to address both race/ethnicity and nativity (REN) in a nationally-representative sample of US adults leaving unanswered questions about potentially “parado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
(81 reference statements)
3
49
0
Order By: Relevance
“…This prevented us from being able to compare our findings on the risk for cognitive impairment among the U.S.-born and foreign-born Mexican-Americans to other racial and ethnic groups, as well as other Hispanic groups (such as Cuban, Central and South American, and Caribbean origins). Recent research has found a foreign-born Mexican-American advantage in the risk of cognitive impairment compared to non-Hispanic whites and blacks in a nationally representative sample of older adults in the United States ( Weden et al, 2017 ). However, this analysis did not consider potential differences in the risk for cognitive impairment among foreign-born by gender or age of migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This prevented us from being able to compare our findings on the risk for cognitive impairment among the U.S.-born and foreign-born Mexican-Americans to other racial and ethnic groups, as well as other Hispanic groups (such as Cuban, Central and South American, and Caribbean origins). Recent research has found a foreign-born Mexican-American advantage in the risk of cognitive impairment compared to non-Hispanic whites and blacks in a nationally representative sample of older adults in the United States ( Weden et al, 2017 ). However, this analysis did not consider potential differences in the risk for cognitive impairment among foreign-born by gender or age of migration.…”
Section: Discussionmentioning
confidence: 99%
“…Research has only recently begun to examine how cognitive functioning for older Hispanics may differ by nativity status ( Downer, Garcia, Saenz, Markides, & Wong, 2017 ; Garcia, Downer, et al, 2017 ; Garcia, Saenz, et al, 2017 ; Garcia et al, 2018 ; Hill, Angel, & Balistreri, 2012 ; Hill, Angel, Balistreri, & Herrera, 2012 ; Weden et al, 2017 ). An analysis of the Health and Retirement Study revealed that foreign-born Mexican-Americans had a 36% lower risk for incident cognitive impairment than non-Hispanic whites independent of age, gender, and socioeconomic characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, although it is a population-based sample of Chinese older adults in the United States, the generalizability of study findings may not go beyond the greater Chicago area, where the PINE study participants were recruited. Third, other factors, that are not included in this study, such as geographic locations, neighborhood conditions, may also affect activity engagement and cognitive function, or serve as the mechanisms through which activities affect cognition ( Weden et al, 2017 ). Finally, our measures might not be inclusive; for example, the cognitive tests did not capture the full range of cognitive abilities, and clinical evaluations of cognitive impairment were missing.…”
Section: Discussionmentioning
confidence: 99%
“…Acculturation is associated with healthy behaviors, such as greater exercise and leisure physical activity; yet, high levels of acculturation are also associated with increased rates of cancer, infant mortality, and poor physical and mental health among Latinos (see Abraído-Lanza et al, 2006 ). The literature inconsistence implies that the immigrant health paradox may be explained by health selection, sociocultural protection, and other mechanisms ( Jasso, Massey, Rosenzweig, & Smith, 2004 ; Weden et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%